Fulfilling the Restitution Rights of Victims of Human Trafficking: A Perspective of Justice - Karim, Abdul (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
Trafficking in persons is a severe crime that harms victims' physical, psychological, and economic well-being. A key part of addressing this issue is ensuring victims receive restitution. However, fulfilling restitution rights remains challenging and often falls short of delivering justice to victims. This study examines these challenges from a justice perspective, highlighting issues such as unclear legal provisions, a lack of victim-centered approaches in court rulings, and difficulties in accessing and implementing restitution. The study recommends improving the PTPPO Law, enhancing victim-focused perspectives in the judiciary, and providing better support for victims to access restitution. These steps are crucial to ensure justice is more effectively served for trafficking victims.